Economic-environmental equilibrium based optimal scheduling strategy towards wind-solar-thermal power generation system under limited resources. (1st December 2018) - Xu, Jiuping; Wang, Fengjuan; Lv, Chengwei; Huang, Qian; Xie, Heping
Highlights: Multi-objective model for wind-solar-thermal power generation system is proposed. Trade-offs between economic benefit and environmental impact is analyzed. 12 scheduling scenarios to handle natural limits of renewable sources are considered. Real case in China to demonstrate the model practicality and efficiency is presented. Abstract: The integration of renewable sources into traditional power networks through the development of hybrid systems has attracted increasing international attention. However, simultaneously considering the environmental impacts, the economic benefits, and the natural limits of renewable sources in hybrid systems has proven difficult. This paper proposes an optimal scheduling strategy that fully considers the contributions of wind farm, solar parks, and coal thermal power plants to determine economic benefit and environmental impact equilibrium in a hybrid generation system under natural limitations. By factoring in the seasonal fluctuations in wind power, the weather driven characteristics of solar power, and the fuzzy coal thermal plant parameters, the optimal strategy better depicts the system characteristics than current strategies. A case study from Hami, China is presented to demonstrate the practicality and efficiency of the optimization model. The calculation results for twelve scheduling scenarios under different wind speeds and weather conditions found that this multi-objective strategy for hybrid generation systems was a superior method for solving the conflicts between emissions reduction and profits under natural renewable source limitations. Compared with previous studies, the optimal strategy this paper proposed is more applicable for developing countries such as China, and provide system operators with less calculation burdens. Management recommendations including the application of equilibrium scheduling strategy, policy support from the government, and improvements in solar power installed capacity have also been proposed.